Effects of Polychlorinated Biphenyl Congener Concentration and Sediment Supplementation on Rates of Methanogenesis and 2,3,6-Trichlorobiphenyl Dechlorination in an Anaerobic Enrichment - Boyle, Alfred W. (1993)
We have employed a method of enrichment that allows us to significantly increase the rate of reductive polychlorinated biphenyl (PCB) dechlorination. This method shortens the time required to investigate the effects that culture conditions have on dechlorination and provides an estimate of the potential activity of the PCB-dechlorinating anaerobes. The periodic supplementation of sterile sediment and PCB produced an enhanced, measurable, and sustained rate of dechlorination. We observed volumetric rates of the dechlorination of 2,3,6-trichlorobiphenyl (2,3,6-CB) to 2,6-dichlorobiphenyl (2,6-CB) of more than 300 μmol liter(-1) day(-1) when the cultures were supplemented daily. A calculation of this activity that is based on an estimate of the number of dechlorinating anaerobes present indicates that 1.13 pmol of 2,3,6-CB was dechlorinated to 2,6-CB day(-1) bacterial cell(-1). This rate is similar to that of the reductive dechlorination of 3-chlorobenzoate by Desulfomonile tiedjei. Methanogenesis declined from 585.3 to 125.9 μmol of CH(4) liter(-1) day(-1), while dechlorination increased from 8.2 to 346.0 μmol of 2,3,6-CB dechlorinated to 2,6-CB liter(-1) day(-1).